Transcriptional profiling identifies IL-33-expressing intestinal stromal cells as a signaling hub poised to interact with enteric neurons - Topczewska, Patrycja M.; Savvopoulou, Anna; Cosovanu, Catalina; Klose, Christoph S. N. (Frontiers in Cell and Developmental Biology, 2024)
Recent advancements in mucosal immunology have unveiled a complex network of intercellular connections within diverse tissues, shedding light on the unique properties of different cell types. Central to this intricate network is the cytokine IL-33, which has gained significant attention for its critical role in various diseases, from allergy to cancer, triggering type 2 immune responses, among others. Recent research has challenged the prior assumptions attributing IL-33 expression to epithelial cells, highlighting stromal cells as the predominant source in adipose tissue and the lungs. However, in the complex landscape of the intestine, where IL-33 plays a crucial role in mediating immune surveillance and tolerance and is implicated in many gut-related disorders, its primary source, regulation, and main characteristics need more exploration. This study identifies stromal cells as the primary IL-33-expressing cell type in the small intestine. By investigating their transcriptome and intrinsic signaling pathways, we have uncovered a possible role of IL-33+ stromal cells in maintaining the stem cell niche and their potential crosstalk with neurons relevant to the regulation of axonogenesis. Importantly, our experiments have demonstrated that vasoactive intestinal peptide stimulation of a primary intestinal stromal cell culture significantly amplifies IL-33 expression on mRNA and protein level. Therefore, our study represents a significant leap forward in understanding the plethora of interactions IL-33+ intestinal stromal cells maintain in the intestine, paving the way for future investigations into stromal-neuro crosstalk in the gut. These findings hold great promise for developing targeted therapeutic strategies aimed at harnessing the potential of IL-33 across a spectrum of diseases.